Assessment in Sport and Exercise Psychology: Considerations and Recommendations for Translation and Validation of Questionnaires - Cid, Luis; Monteiro, Diogo; Teixeira, Diogo Santos; Evmenenko, Anastasiia; Andrade, Ana; Bento, Teresa; Vitorino, Anabela; Couto, Nuno; Rodrigues, Filipe (Frontiers in Psychology, 2022)
Translating and validating measurement instruments in sport and exercise psychology is not an easy task. Rather, it is a task that requires effort and time, for the process is not limited to a simple translation to translate words from one language to another, just in order to make valid and reliable measure. All researchers should be aware that the only proper way is to adopt rigorous and robust methodologies to conduct the process from the preliminary stage of translation to reaching the validitation stage of the psychological variable. Only so is it possible to avoid creating fragile and inadequate psychological assessment instruments that can jeopardize the entire investigation to be held with its use. Thus, the main objective of this work is to promote reflection and discussion on the subject by presenting some considerations and recommendations about translation and validation of questionnaires for psychological assessment applied to sport and exercise domain.